The Neural Bases of Taxonomic and Thematic Conceptual Relations: An MEG Study - Lewis, Gwyneth A. (Neuropsychologia, 2015)
Converging evidence from behavioral and neuroimaging studies of human concepts indicate distinct neural systems for taxonomic and thematic knowledge. A recent study of naming in aphasia found involvement of the anterior temporal lobe (ATL) during taxonomic (feature-based) processing, and involvement of the temporoparietal junction (TPJ) during thematic (function-based) processing. We conducted an online magnetoencephalography (MEG) study to examine the spatio-temporal nature of taxonomic and thematic relations. We measured participants’ brain responses to words preceded by either a taxonomically or thematically related item (e.g., cottage→castle, king→castle). In a separate experiment we collected relatedness ratings of the word pairs from participants. We examined effects of relatedness and relation type on activation in ATL and TPJ regions of interest (ROIs) using permutation t-tests to identify differences in ROI activation between conditions as well as single-trial correlational analyses to examine the millisecond-by-millisecond influence of the stimulus variables on the ROIs. Taxonomic relations strongly predicted ATL activation, and both kinds of relations influenced the TPJ. Our results further strengthen the view of the ATL's importance to taxonomic knowledge. Moreover, they provide a nuanced view of thematic relations as involving taxonomic knowledge.